О некотором подходе к исследованию профессионального одиночества у сотрудников государственной службы Украины по чрезвычайным ситуациям - Dovbiy, Т. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article presents the results of the study of the causes and features of display state of «professional loneliness» in the emergency and rescue units SSES Ukraine arising as a reaction on the extreme conditions of professional activity. Based on the analysis of eight main theoretical approaches and categorical apparatus on the problem of loneliness and studied specific professional rescuers, the definition of the concept of «professional loneliness», has been given; it describes the characteristics of the individual selected for the manifestation of its forms: constructive and destructive. A structured scheme related to the concepts of loneliness: «isolation», «solitude», «exclusion» and «depression» has been provided. The findings of a task to build a 3-dimensional semantic space of the concept of «loneliness», identified 10 associated attributes (basic mental states) have been presented that are to be the primary diagnosis to provide psychological support to rescuers.